Humble Leadership in Education: A Systematic Review and Future Direction - Vergiansyah, Ivan; Supriharyanti, Elisabeth; Nadia, Fiona Niska Dinda (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this study is to systematically review previous research on humble leadership, which is new in the educational context. This study is to fill the gap in the literature and become a comprehensive understanding of positive leadership types in overcoming arrogance and narcissistic issues that exist in the scope of education by discussing the contributions and emphasizing the main issues of previous research related to conceptual humble leadership which is explained through behavioral dimensions, the development of the concept of humble leadership in the educational context, the use of theories used, methodology, antecedent and consequence. This research searched all publications that examined humble leadership published from 2012 - 2024. A total of 18 studies from 261 articles were found from the Scopus database. This research found that humble leadership is a new leader approach that uses few theoretical sources in defining the concept of humble leadership. In addition, the findings of this study also successfully established some factors that shape humble leadership as antecedents and the impact of humble leadership in the educational context. However, this literature review only used 1 database so that future research can expand the range of articles reviewed using other data sources.